Effective coaching in football - Nash, C.; Mallett, C. J. (Football Psychology - From Theory to Practice, 2019)
Coaches are held totally responsible and accountable for performance outcomes in football. Although this high degree of accountability might seem appropriate to the media and public at large, the reality of understanding effective coaching is more muddied. Effective coaching is complex and multifaceted and occurs within a chaotic, unpredictable, and often uncontrollable environment; that is, it is characterised by an incongruency between intended performance goals and actual results (Jones & Wallace, 2005). The emphasis on winning and the context of football coaching contribute to problematising effective coaching. Therefore, in this chapter, we highlight the problematic nature of judging coaching effectiveness; for example, the varying criteria for assessing coaching effectiveness. Furthermore, we considered the definition of coaching effectiveness in terms of athletes` outcomes, coaches` knowledge, and the saliency of context (Cote & Gilbert, 2009). Coaches have obligations to help players flourish through football and contribute to both professional and personal development. These developmental outcomes are contingent upon the quality of the coaching experience. The discussion on the complexity of coaches` work, the differing tasks and roles of a football coach, will hopefully invite coaches to question and reflect on their current practices, and consider the nature of their impact on players, and what is the evidence of that impact. Finally, effective football coaches should strive to be lifelong learners to provide football players with quality sporting experiences.